Collateral Status on Baseline Computed Tomographic Angiography and Intra-Arterial Treatment Effect in Patients With Proximal Anterior Circulation Stroke. Issue 3 (March 2016) - Berkhemer, Olvert A.; Jansen, Ivo G.H.; Beumer, Debbie; Fransen, Puck S.S.; van den Berg, Lucie A.; Yoo, Albert J.; Lingsma, Hester F.; Sprengers, Marieke E.S.; Jenniskens, Sjoerd F.M.; Lycklama à Nijeholt, Geert J.; van Walderveen, Marianne A.A.; van den Berg, René; et al.
Abstract : Background and Purpose—: Recent randomized trials have proven the benefit of intra-arterial treatment (IAT) with retrievable stents in acute ischemic stroke. Patients with poor or absent collaterals (preexistent anastomoses to maintain blood flow in case of a primary vessel occlusion) may gain less clinical benefit from IAT. In this post hoc analysis, we aimed to assess whether the effect of IAT was modified by collateral status on baseline computed tomographic angiography in the Multicenter Randomized Clinical Trial of Endovascular Treatment of Acute Ischemic Stroke in the Netherlands (MR CLEAN). Methods—: MR CLEAN was a multicenter, randomized trial of IAT versus no IAT. Primary outcome was the modified Rankin Scale at 90 days. The primary effect parameter was the adjusted common odds ratio for a shift in direction of a better outcome on the modified Rankin Scale. Collaterals were graded from 0 (absent) to 3 (good). We used multivariable ordinal logistic regression analysis with interaction terms to estimate treatment effect modification by collateral status. Results—: We found a significant modification of treatment effect by collaterals ( P =0.038). The strongest benefit (adjusted common odds ratio 3.2 [95% confidence intervals 1.7–6.2]) was found in patients with good collaterals (grade 3). The adjusted common odds ratio was 1.6 [95% confidence intervals 1.0–2.7] for moderate collaterals (grade 2), 1.2 [95% confidence intervals 0.7–2.3] for poor collaterals (grade 1), and 1.0 [95% confidence intervals 0.1–8.7] for patients with absent collaterals (grade 0). Conclusions—: In MR CLEAN, baseline computed tomographic angiography collateral status modified the treatment effect. The benefit of IAT was greatest in patients with good collaterals on baseline computed tomographic angiography. Treatment benefit appeared less and may be absent in patients with absent or poor collaterals. Clinical Trial Registration—: URL:http://www.trialregister.nl andhttp://www.controlled-trials.com . Unique identifier: (NTR)1804 and ISRCTN10888758, respectively. Abstract : Supplemental Digital Content is available in the text.